Winter diet composition of urban long-eared owls (Asio otus) in Rzeszów (SE Poland) - Dziemian, Sylwia; Piłacińska, Barbara; Pitucha, Grzegorz (Adam Mickiewicz University Poznan, 2013)
Diet variation of the long-eared owl (Asio otus Linnaeus, 1758) was investigated on the basis of pellets collected in winter season 2007/2008 from a communal roosting site in a municipal cemetery in Rzeszów (a city in south-eastern Poland). We assumed that the proximity of human settlements would affect the diet composition of this predator, resulting in a higher proportion of species associated with urban habitats. Although voles, especially the common vole Microtus arvalis, were still the most important prey, mice constituted approximately 17% of all prey items, with the field mouse Apodemus agrarius being most frequent. Food niche breadth was wider in December than in March. Our results suggest that owls from Rzeszów hunt mostly in open habitats surrounding the city, where they can still capture their basic prey species. Yet, they can broaden their diet with species of murids associated with the mosaic urban and suburban habitats.